Your inner fish : A Journey into the 3-5 billion year history of the human body - Shubin, Neil. (London : Allen Lane, 2008)
Neil Shubin, a leading paleontologist and professor of anatomy who discovered Tiktaalik--the "missing link" that made headlines around the world in April 2006--tells the story of evolution by tracing the organs of the human body back millions of years, long before the first creatures walked the earth. By examining fossils and DNA, Shubin shows us that our hands actually resemble fish fins, our head is organized like that of a long-extinct jawless fish, and major parts of our genome look and function like those of worms and bacteria.
Finding your inner fish -- Getting a grip -- Handy genes -- Teeth everywhere -- Getting ahead -- The best-laid (body) plans -- Adventures in bodybuilding -- Making scents -- Vision -- Ears -- The meaning of it all -- Epilogue.
Includes index.
Keywords: Human evolution -- Popular works; Human anatomy -- Popular works; Evolution -- Human